Produk Susu Kefir Sari Buah Pisang Starter Japannese Cristal Algae Untuk Peningkatan Ketahanan Pangan Di Daerah Perbatasan RI-RDTL - Bouk, Gomera; Sinabang, Maria Kristina; K. Bere, Edelnia; Dewi, Yelsi Listiana (Universitas Islam Kadiri, 2024)
Kefir is a fermented milk product using lactic acid bacteria and yeast which has a distinctive sour and alcoholic taste. The study was conducted in July-October 2023. The research was conducted at the Laboratory of Animal Product Technology at Ben Mboi Polytechnic, Kakuluk Mesak District, Belu Regency, East Nusa Tenggara Province and the Feed Chemistry Laboratory, Faculty of Animal Husbandry, Nusa Cendana University-Kupang. With the aim of knowing the characteristics of milk kefir by utilizing Japanese algae crystals as milk fermenation materials and to determine the chemical quality of kefir milk products added with plantains as one of the functional food products. This study used experimental methods, and the research design used Complete Randomized Design (RAL) factorial patterns. The first factor is the composition of the material consisting of components: K1=Japanese Algae:Banana:Sugar:Milk (50g:50g:10g:500ml), K2= Japanese Algae:Banana: Sugar:Milk (75g:75g:20g:750ml), and K3= Japanese Algae:Banana:Sugar:Milk (100g:100g:30g:1000ml). The second factor is Storage duration which consists of: L1 = Storage length 24 hours, L2 = Storage length 48 hours and L3 = Storage length 72 hours, so there are 9 combinations. The results showed that the combination of treatment of the composition of kefir milk forming ingredients and storage duration had a significant effect on the chemical quality of kefir milk. The best treatment is shown in the combination of K3L1 treatment, namely the composition of kefir milk forming ingredients from Japanese algae: Banana: Sugar: Milk (100g: 100g: 30g: 1000ml) with the best protein content (4.77 ± 0.334), low alcohol content values (0.31 ± 0.065) and pH of 5.63 ± 0.115.